EFFECTIVENESS OF THE FAMILY HEALTH STRATEGY IN BAHIA - Martins Ribeiro, Alessandro; Miranda Lago, Vivian; Silveira Tolentino Júnior, Dilceu; Silene Lopes de Souza Albuquerque, Katia (Health and Society, 2022)
Objective: to know the evolution of effective programs and actions in primary care through public health policies for the family health strategy (FHS) and point out which are the programs and actions in primary care in preventive health for the Baiana population. Methodology: A systematic review was conducted with the objective of answering “Which are the health policies in primary care that were effective in the incorporation of the ESF in Bahia?” in the SciELO, LILACS and MEDLINE bases using the descriptors “Estratégia Saúde da Família”; “Atenção Primária”; “Bahia” in the Portuguese language, in national journals such as Cadernos de Saúde Pública CPS, Brazilian Journal of Health Review, Ciência & Saúde Coletiva, Revista Brasileira de Enfermagem. Results and Discussion: In view of the analysis of the articles and according to the authors, the Public Policies effective in primary care that were most consolidated were: the Popular Pharmacy, Integrative and Complementary Health Practices (PICS), Community Health Agents (ACS), Smiling Brazil, Municipal Health Councilors (CMS), HiperDia Program, More Doctors Program (PMM), Hospitalizations for Conditions Sensitive to Primary Care (ICSAP), Pact for Life and Health at School Program (PSE). Concluding remarks: Therefore, added to the historical facts and the improvements in programs and actions developed in Bahia it is possible to conclude that primary health mediated by the ESF allowed the pathological diagnosis to any Baiano, to be made early and with that his sexual, emotional, nutritional and physical life could be oriented and assisted in its integrality.